Perceived key determinants of payment instrument usage: a fuzzy cognitive mapping-based approach - Santos, F. R. R. L. (2018)
The recent economic climate has had direct repercussions on people’s daily lives. This has occurred not only in how they use payment instruments, but is also evinced in new concerns adjacent to technological advances, people’s safety and the credibility of financial institutions. In this regard, the banking sector has had a crucial role in countries’ economic development, making it increasingly important to understand how the banking system operates and what payment instruments are available to users. Relying on specialized literature and the application of fuzzy cognitive mapping, this study aims to understand the cause-and-effect relationships between customers’ preference factors in using payment instruments. The results show that usability aspects and safety concerns constitute the factors which users pay more attention to. Strengths and limitations of our proposal are also discussed.